Effect of wrist and finger flexion in relation to strain on the tendon origin of the extensor carpi radialis brevis: A cadaveric study simulating stretching exercises. (November 2017) - Shirato, Rikiya; Aoki, Mitsuhiro; Iba, Kousuke; Wada, Takuro; Hidaka, Egi; Fujimiya, Mineko; Yamashita, Toshihiko
Abstract: Background: Stretching exercises based on wrist flexion-ulnar deviation with elbow extension, forearm pronation, and additional index or middle finger flexion have been used to stretch the wrist extensors for lateral epicondylitis. The purpose of this study was to quantify the strain on the tendon origin of the extensor carpi radialis brevis in cadaver specimens during these stretching exercises. Methods: We used 8 fresh frozen/thawed cadaveric upper extremities. The strain on the extensor carpi radialis brevis tendon origin was measured by the addition of 4 types of traction (no traction, wrist flexion-ulnar deviation, and index or middle finger flexion in combination with wrist flexion-ulnar deviation) in 7 sequential elbow flexion angles during forearm pronation. Two types of varus stress load to the elbow (none, gravity on the forearm) were also applied. Findings: A significant increase in strain was obtained by wrist traction with 0°, 15° and 30° of elbow flexion ( P  < 0.05). The strain was also significantly increased by adding finger traction ( P  < 0.05) and varus stress load ( P  < 0.05). A maximum strain value of 5.30 (SD 1.73) % was obtained when traction on the middle finger in combination with traction of the wrist was added at 15° elbow flexion with varus stress load. Interpretation: The present study provides data about the amount of strain on the extensor carpi radialis brevis tendon during stretching exercises of the wrist and finger extensors. The results of this study could be applied to stretching exercises for patients with lateral epicondylitis. Highlights: Strain on the extensor carpi radialis brevis tendon in cadavers Wrist flexion-ulnar deviation produced a large strain. The strain was also increased by adding finger flexion, and elbow varus stress. A maximum strain value of 5.30% was obtained.